Hubungan Pengetahuan dan Sikap Ibu dengan Pemberian Asi Eksklusif di Klinik Bersalin Evie Kec Babalan Kabupaten Langkat Tahun 2022 - Damayanty S; Marta Armita Silaban; Ika Damayanti Sipayung; Ade Rachmat Yudianto (Lembaga Pengembangan Kinerja Dosen, 2022)
According to WHO data (2016), the coverage of exclusive breastfeeding worldwide was only around 36% during the 2007-2014 period. The achievement of exclusive breastfeeding in Indonesia in 2016 was 54%, but again decreased in 2017 to only 35% (Ministry of Health RI, 2017). In accordance with Health Law No. 36 of 2009 article 128 paragraph 1 states that every baby has the right to get exclusive breastfeeding from birth for six months except for medical indications and in paragraph (2) it says